A method and device for continuous lithium extraction by magnetic field assisted two-chamber flow electrode circulation

By designing core-shell structured magnetic electrode particles Fe3O4@C@LiMn2O4 and optimizing the external magnetic field, the problems of complex electrode preparation and the contradiction between suspension density and efficiency in the traditional electrochemical method of lithium extraction were solved. This enabled efficient, stable and continuous lithium extraction under low slurry density, thereby improving the utilization value of low-grade lithium resources.

CN123027451APending Publication Date: 2026-11-03TIANJIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611509777.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-28
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Traditional fixed electrodes in brine lithium extraction suffer from problems such as complex preparation, high energy cost, hindered lithium ion diffusion, reduced electrode capacity, and poor stability. Flow electrode systems, on the other hand, face the challenges of balancing suspension density and efficiency, and time-consuming solid-liquid separation. Existing magnetic field-assisted schemes have failed to effectively achieve continuous and stable cyclic lithium extraction during the reaction process.

Method used

The design is adapted to low-concentration core-shell structure magnetic electrode particles Fe3O4@C@LiMn2O4. By combining an external magnetic field and optimized operating parameters, efficient mass transfer under low slurry density is achieved. The system is kept stable through continuous feeding and closed-loop circulation. The design is adapted to achieve an efficient, stable and continuous lithium extraction process under low slurry density.

Benefits of technology

It achieves efficient mass transfer at low slurry density, with a lithium extraction rate of 87.32% and a charge efficiency of over 86%. It simplifies slurry formulation, reduces material costs, and is applicable to various lithium-containing solution systems, with significant advantages, especially in the extraction of low-concentration lithium resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123027451A_ABST
    Figure CN123027451A_ABST
Patent Text Reader

Abstract

The present application relates to electrochemistry technology, disclose a kind of magnetic field assisted double-chamber flow electrode continuous circulation lithium extraction method and device.The method is that magnetic electrode material Fe3O4@C@LiMn2O4 and conductive agent are added into recovery liquid and lithium-containing brine respectively to prepare anode and cathode flow electrode slurry, and is delivered to double-chamber reactor by peristaltic pump;Under the action of external power supply and magnetic field, lithium ion is selectively inserted into lithium-poor state magnetic electrode material in cathode chamber, lithium ion is released to recovery liquid by lithium-rich state material in anode chamber, and anion migrates through ion exchange membrane to maintain charge balance, and after reaction, slurry returns to storage tank, and solid-liquid separation is realized using magnetic response characteristics, and the electrode material after separation is recycled, to form continuous closed circuit lithium extraction system.The present application can realize efficient mass transfer under low slurry solid content, and lithium extraction rate reaches 87.32%, and is suitable for salt lake brine, seawater and lithium-containing waste liquid and other various systems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to electrochemical technology, and more particularly to a method and apparatus for continuous cyclic lithium extraction using a magnetic field-assisted dual-chamber flow electrode. Background Technology

[0002] With the rapid development of the global lithium-ion battery market, the demand for lithium resources continues to grow, driving an urgent need for efficient and sustainable lithium extraction technologies. Brine resources, due to their high lithium content and abundant reserves, have become an important source of lithium extraction. Current brine lithium extraction technologies mainly include precipitation, solvent extraction, membrane separation, and electrochemical methods. Among these, electrochemical lithium extraction has become a research hotspot in recent years due to its excellent selectivity, low energy consumption, and high recyclability.

[0003] However, traditional electrochemical lithium extraction technology, which mainly relies on fixed electrodes, still has several problems. First, the electrode preparation process is complex and energy-intensive, involving electrode slurry mixing, slurry coating, and solvent evaporation. Second, the use of the hydrophobic binder PVDF (polyvinylidene fluoride) hinders lithium-ion diffusion within the electrode, thus reducing the system's capacity and extraction rate. Furthermore, fixed electrodes may crack and detach during long-term use, leading to a decrease in electrode capacity. Moreover, the lithium-intercalating active material of the fixed electrode gradually degrades due to structural degradation and loss of active sites during long-term operation in a brine environment, making it difficult to maintain stable lithium extraction performance.

[0004] To address the challenges associated with traditional fixed electrodes, a flow electrode capacitive deionization (FCDI) system is proposed. FCDI offers advantages such as high selectivity, low energy consumption, and strong solution adaptability. The flow electrode slurry is mainly composed of capacitive carbon-based materials or pseudo-capacitive materials suspended in the electrolyte.

[0005] The FCDI system has the following limitations. First, FCDI devices require a high suspension density of the flowing electrode slurry. High suspension density increases the collision probability between the active material and the current collector, improving the efficiency of lithium ion insertion and extraction on the active material surface. However, a high suspension density of the flowing electrode slurry can easily lead to device clogging, while reducing the suspension density reduces the efficiency of lithium ion insertion and extraction, creating an irreconcilable contradiction. Second, after the lithium-depleted material in the flowing electrode slurry has achieved the required lithium extraction or the lithium-rich material in the anode flowing electrode slurry has achieved the required delithiation, a solid-liquid separation device is needed for solid-liquid separation. This process is time-consuming and energy-intensive, making it difficult to meet the requirements for continuous operation.

[0006] To balance the relationship between the suspension density of the flow electrode and the lithium extraction efficiency, researchers have attempted to introduce a magnetic field into the FCDI system. However, existing magnetic field-assisted methods mainly focus on improving ion migration efficiency or conductivity, and a systematic solution is still lacking for how to utilize a magnetic field to simultaneously achieve particle motion control and continuous and stable cyclic lithium extraction during the reaction process. Summary of the Invention

[0007] To overcome the shortcomings of existing technologies, this invention provides a magnetic field-assisted dual-chamber flow electrode continuous cyclic lithium extraction method and apparatus. By designing and adapting to low-concentration core-shell structure magnetic electrode particles and optimizing operating parameters, it achieves efficient mass transfer at low slurry density and maintains stable lithium-ion concentration in the system through continuous feeding and closed-loop circulation, thereby realizing an efficient, stable and continuous lithium extraction process.

[0008] The technical solution of this invention is: This invention provides a method for continuous cyclic lithium extraction using a magnetic field-assisted dual-chamber flow electrode, comprising the following steps: (1) Slurry preparation: The magnetic electrode material and conductive agent are added to the recovery liquid and mixed evenly to obtain the anode flow electrode slurry. The lithium-poor magnetic electrode material obtained by delithiation treatment is added to lithium-containing brine and mixed evenly to obtain a cathode flow electrode slurry; the magnetic electrode particles are Fe3O4@C@LiMn2O4 and the mass ratio of Fe3O4@C to LiMn2O4 is 1:2 to 1:7. (2) The cathode flow electrode slurry and the anode flow electrode slurry are respectively delivered to the cathode chamber and the anode chamber by a peristaltic pump; (3) Under the action of an external power supply and a magnetic field, the lithium-depleted magnetic electrode material in the cathode chamber selectively inserts lithium ions from the lithium-containing brine, and the magnetic electrode material in the anode chamber undergoes a delithiation reaction, releasing lithium ions into the recovery liquid. At the same time, anions migrate through the ion exchange membrane to maintain the charge balance in the cathode and anode chambers. The magnetic field is provided by a magnetic field generating device located on both sides of the anode and cathode chambers, and the magnetic field strength is 10 to 30 mT. The operating voltage of the external power supply is 0.5 to 2.0 V. (4) The anolyte and cathode slurry after the reaction are returned to their respective storage tanks and separated by a solid-liquid separation device using the magnetic response characteristics of the magnetic electrode material. (5) The lithium-poor brine obtained from the separation is discharged and collected. The delithiated magnetic electrode material is mixed with the newly replenished lithium-containing brine and returned to the cathode tank. The lithium-rich recovery liquid obtained from the separation is collected. The lithium-intercalated magnetic electrode material is mixed with the recovery liquid and returned to the anode tank for delithiation. (6) Continuously replenish lithium-containing brine to the cathode tank to replenish the lithium ion loss caused by continuous lithium resource extraction, maintain the stable concentration of lithium ions in the system, and form a continuous closed-loop lithium extraction system.

[0009] Preferably, the method for preparing the magnetic electrode material includes: 1) The preparation method of Fe3O4@C particles is as follows: 300 mL of anhydrous ethanol and 700 mL of deionized water are mixed, and 20 g of hexadecyltrimethylammonium bromide is added; after ultrasonic treatment for 1 h, the mixture is further mixed by mechanical stirring for 30 min, and then the self-made Fe3O4 particles are added. 3 mL of NH4OH is added to the mixed solution under vigorous mechanical stirring; after vigorous stirring for 1 h, 4.0 g of resorcinol and 6 mL of formaldehyde solution are added. Subsequently, the mixture is placed at room temperature and stirred by mechanical stirring for 24 h. Fe3O4@resorcinol-formaldehyde (Fe3O4@RF) resin composite material is obtained by magnetic separation. The mixture is washed several times with deionized water and anhydrous ethanol until the supernatant is completely clear, and then dried in a vacuum drying oven at 60 ℃ for 12 h. Finally, the Fe3O4@RF resin composite material is carbonized in a horizontal tube furnace. The inert gas atmosphere during the carbonization process is a high-purity nitrogen atmosphere, and the heating rate during the heating process is 2 ℃·min. -1 The carbonization time was 3 hours. The resulting material was named Fe3O4@C particles.

[0010] 2) Add Fe3O4@C particles to deionized water, then add lithium hydroxide monohydrate, stir, add potassium permanganate, ascorbic acid and anhydrous ethanol, react at room temperature, then transfer to a reaction vessel for hydrothermal reaction at 150-200 ℃ for 3-8 h. After the reaction is completed, magnetic separation, washing and drying are performed to obtain magnetic electrode material (Fe3O4@C@LiMn2O4).

[0011] Preferably, the magnetic field strength is 10.19-25.02 mT, and more preferably 20.12 mT.

[0012] Preferably, the operating voltage of the external power supply is 0.5 to 1.5 V, and more preferably 1.0 V.

[0013] Preferably, the solid content of the magnetic electrode material and the conductive agent in the anolyte slurry is 1.0-5.0 wt% and 0.5-1.5 wt%, respectively, and the electrolyte content is 10-300 mg·L⁻¹. -1 LiCl solution.

[0014] Preferably, the solid content of the lithium-depleted magnetic electrode material and the conductive agent in the cathode flowing electrode slurry is 1.0-5.0 wt% and 0.5-1.5 wt%, respectively, and the electrolyte content is 10-300 mg·L⁻¹. -1 LiCl solution.

[0015] Preferably, the lithium-poor magnetic electrode material is obtained by placing a magnetic electrode material in an HCl solution for lithium removal, with the chemical formula Fe3O4@C@HMn2O4.

[0016] Preferably, the circulation rate of the flowing electrode slurry is 0-100 mL / min. -1 .

[0017] Preferably, the lithium-containing brine includes one or more of the following: seawater, concentrated seawater, salt lake brine, concentrated brine, brine pretreated by membrane filtration or solar pond evaporation, and lithium-containing waste liquid recovered after lithium battery production or use. The recovered liquid is pure water or lithium salt solutions of different concentrations.

[0018] Another aspect of the present invention provides a lithium extraction apparatus for realizing the above-mentioned magnetic field-assisted dual-chamber flowing electrode continuous circulation lithium extraction method, comprising a dual-chamber reactor, a current collector, a magnetic field generating device, and a material circulation system connecting a cathode chamber and an anode chamber; the dual-chamber reactor is divided into an anode chamber and a cathode chamber by an anion exchange membrane, and current collectors are respectively arranged on both sides of the cathode chamber and the anode chamber; the magnetic field generating device is placed outside the current collector, and the magnetic field generating device includes one of a permanent magnet, a solenoid, a Helmholtz coil, and an electromagnet, and when the magnetic field generating device is an electromagnetic magnetic field generating device, it is connected to a magnetic field power supply; the material circulation system connecting the cathode chamber and the anode chamber includes a cathode tank, an anode tank, a feed brine storage tank, a recovery liquid storage tank, and a solid-liquid separation device, the anode tank is connected to the anode chamber through a pipeline, and the anode flowing electrode slurry is placed in the anode tank; the cathode tank is connected to the cathode chamber through a pipeline, and the cathode flowing electrode slurry is placed in the cathode tank.

[0019] Preferably, both the anode chamber and the cathode chamber are provided with liquid inlets and outlets, and the electrode slurry is transported from the cathode tank and the anode tank to the flow channel of the corresponding chamber by a peristaltic pump at a preset flow rate, so as to ensure stable circulation and efficient mass transfer of the slurry.

[0020] Preferably, the anion exchange membrane is composed of a polymer matrix with fixed positively charged groups, and is a sieving membrane that allows chloride ions to pass through. Quaternary ammonium groups and other positively charged groups within the membrane form fixed cation sites, attracting anions (such as Cl-) from the solution. - Anion exchange membranes can repel cations, while simultaneously rejecting cations. They can be either homogeneous or heterogeneous.

[0021] Preferably, the cathode tank and anode tank are equipped with a stirring system to continuously stir the mixed electrode slurry at a speed of 10-3500 rpm.

[0022] Preferably, the current collector is a serpentine flow channel graphite plate with an electrode area of ​​18.92 cm². 2 .

[0023] The core innovation of this invention lies in the design of a Fe3O4@C@LiMn2O4 core-shell magnetic electrode material, integrating magnetic response and lithium intercalation activity into a single particle. The Fe3O4 core endows the particle with magnetic response characteristics, the intermediate carbon layer improves interfacial contact and electron transport, and the LiMn2O4 shell provides lithium-ion intercalation / deintercalation sites. This particle simultaneously performs the dual functions of lithium intercalation / deintercalation reaction and magnetic field response in a dual-chamber system, eliminating the need for additional magnetically conductive additives. Furthermore, the magnetic field is simultaneously used for particle motion control during the reaction stage and for solid-liquid separation after the reaction. Combined with continuous feeding and closed-loop circulation, a continuous cyclic lithium extraction system of "cathode lithium intercalation—anode deintercalation—magnetic field separation—particle recovery—continuous feeding" is constructed, achieving efficient, stable, and continuous lithium extraction at relatively low slurry densities.

[0024] The advantages and beneficial effects of this invention are: (1) This invention achieves a lithium extraction rate of 87.32% by driving magnetic electrode particles to migrate directionally towards the current collector using a magnetic field, with a solid content of only 3.0 wt% in the magnetic electrode material. This eliminates the need for high-density slurry to achieve efficient mass transfer, fundamentally avoiding channel blockage and pumping difficulties caused by high-density slurry. A continuous closed-loop lithium extraction system is formed through slurry circulation, magnetic field separation, and continuous feeding. The lithium extraction rate remains above 78% and the charge efficiency remains above 86% within 10 cycles.

[0025] (2) By optimizing the mass ratio of Fe3O4@C to LiMn2O4 and the solid content of the slurry, the optimal balance between magnetic responsiveness and lithium intercalation capacity, lithium extraction performance and slurry flowability was achieved. In the reaction stage, the magnetic field drives the particles to migrate towards the current collector; in the separation stage, the same magnetic responsiveness is used to achieve rapid particle separation with a recovery rate of ≥95%. One magnetic field generating device serves two functions. The separated magnetic electrode material can be directly recycled without complex operations such as filtration and centrifugation, and without the need for additional magnetic conductive additives, simplifying the slurry formulation and reducing material costs. It is suitable for various lithium-containing solution systems such as seawater, salt lake brine, industrial lithium-containing waste liquid and synthetic simulated brine, and has significant advantages, especially in the extraction of low-concentration lithium resources, thus improving the utilization value of low-grade lithium resources. Attached Figure Description

[0026] Figure 1 This is a process flow diagram of the magnetic field-assisted dual-chamber flow electrode continuous cyclic lithium extraction method of the present invention.

[0027] Figure 2 This is a schematic diagram of the apparatus for realizing the magnetic field-assisted dual-chamber flow electrode continuous cyclic lithium extraction method of the present invention.

[0028] Figure 3 XRD patterns of Fe3O4@C@LiMn2O4 particles prepared with different mass ratios of Fe3O4@C and LiMn2O4.

[0029] Figure 4 The graphs show the lithium removal performance tests conducted by applying different magnetic field strengths for Examples 1, 11, 12, and 13.

[0030] Figure 5 This is a bar chart of the separation coefficients in simulated salt lake brine containing the effects of multiple ions, as shown in Example 14. Detailed Implementation

[0031] To more clearly illustrate the purpose, technical solution, and advantages of this invention, the technical solution of this invention will now be described in detail with reference to specific embodiments. It should be emphasized that the following embodiments are for illustrative purposes only and do not constitute a limitation of this invention. Within the framework of this invention, any modifications, equivalent substitutions, or optimizations implemented by those skilled in the art without creative effort should be considered within the protection scope of this invention.

[0032] To make the technical solution of the present invention clearer, specific examples will be provided below for detailed explanation. However, the content of the present invention is not limited to the scope of the listed embodiments.

[0033] Example 1 A magnetic field-assisted continuous cyclic lithium extraction method using a dual-chamber flow electrode includes the following steps: (1) Slurry preparation: The preparation method of magnetic electrode material includes the following steps: 1) Preparation of Fe3O4@C particles: 300 mL of anhydrous ethanol and 700 mL of deionized water were mixed, and 20 g of hexadecyltrimethylammonium bromide was added. After ultrasonic treatment for 1 h, the mixture was stirred mechanically for 30 min, and then the self-made Fe3O4 particles were added. 3 mL of NH4OH was added to the mixture under vigorous mechanical stirring, and after vigorous stirring for 1 h, 4.0 g of resorcinol and 6 mL of formaldehyde solution were added. The mixture was then placed at room temperature and stirred mechanically for 24 h. Fe3O4@resorcinol-formaldehyde (Fe3O4@RF) resin composite material was obtained by magnetic separation. The composite material was washed several times with deionized water and anhydrous ethanol until the supernatant was completely clear, and then dried in a vacuum drying oven at 60 °C for 12 h. Finally, the Fe3O4@RF resin composite material was carbonized in a horizontal tube furnace. The inert gas atmosphere during carbonization was a high-purity nitrogen atmosphere, and the heating rate was 2 °C·min. -1 The carbonization time was 3 h. Fe3O4@C particles were obtained.

[0034] 2) Add 0.4 g of Fe3O4@C particles to deionized water, add 0.6 g of lithium hydroxide monohydrate, stir for 0.5 h, then add 2.4 g of potassium permanganate, 0.2 g of ascorbic acid and 6 g of anhydrous ethanol. After reacting at room temperature for 2 h, transfer to a 200 mL reactor and react at 180 ℃ for 5 h, with a heating rate of 5 ℃·min. -1 After the reaction was completed, magnetic separation was performed using a magnet, and the supernatant was washed with deionized water and anhydrous ethanol until it was completely clear. The supernatant was then dried in a vacuum drying oven at 60 °C for 12 h. The final result was a magnetic electrode material (Fe3O4@C@LiMn2O4-1:4) with lithium manganese oxide grown in situ outside the carbon layer of Fe3O4@C. The saturation magnetization was 15.32 emu·g. -1 The saturation magnetization intensity reflects the variation in magnitude caused by different mass ratios of Fe3O4@C and LiMn2O4.

[0035] The magnetic electrode material and conductive agent were added to the recovery liquid and mixed evenly to obtain the anode flow electrode slurry. The solid content of the magnetic electrode material in the anode flow electrode slurry was 3 wt%, and the conductive agent was 1.0 wt%.

[0036] The magnetic electrode material Fe3O4@C@LiMn2O4-1:4 was placed in 0.05 mol·L⁻¹ -1Lithium removal was performed in HCl solution for 4 hours to obtain Fe3O4@C@HMn2O4-1:4. The solid content of the lithium-poor magnetic electrode material (Fe3O4@C@HMn2O4-1:4) in the cathode flow electrode slurry was 3 wt%, and the solid content of the conductive agent was 1.0 wt%.

[0037] (2) The cathode flow electrode slurry and the anode flow electrode slurry are respectively delivered to the cathode chamber and the anode chamber by a peristaltic pump; (3) Under the action of an external power supply and a magnetic field, the lithium-depleted magnetic electrode material in the cathode chamber selectively inserts lithium ions from the lithium-containing brine, and the magnetic electrode material in the anode chamber undergoes a delithiation reaction, releasing lithium ions into the recovery liquid. At the same time, anions migrate through the ion exchange membrane to maintain the charge balance in the cathode and anode chambers. The magnetic field is provided by a magnetic field generating device located on both sides of the anode and cathode chambers, and the magnetic field strength provided by the electromagnet is 20.12 mT. The operating voltage of the external power supply is 1.0 V, and the circulation rate of the flowing electrode slurry is 50 mL·min. -1 The electrolyte concentration was 69.41 mg·L⁻¹. -1 LiCl solution; (4) The anolyte and cathode slurry after the reaction are returned to their respective storage tanks and separated into solid and liquid by a solid-liquid separation device using the magnetic response characteristics of the magnetic electrode material. (5) The lithium-poor brine obtained from the separation is discharged and collected. The delithiated magnetic electrode material is mixed with the newly replenished lithium-containing brine (LiCl solution) and returned to the cathode tank. The lithium-rich recovery solution obtained from the separation is collected. The lithium-intercalated magnetic electrode material is mixed with the recovery solution and returned to the anode tank for delithiation. (6) Continuously replenish the cathode tank with lithium-containing brine (LiCl solution) to replenish the lithium ion loss caused by continuous lithium resource extraction, maintain the stable concentration of lithium ions in the system, and form a continuous closed-loop lithium extraction system.

[0038] Example 2 The difference from Example 1 lies only in step 2) of the preparation method of the magnetic electrode material. The mass ratio of Fe3O4@C to LiMn2O4 is 1:2, specifically: 0.4 g of Fe3O4@C particles, 0.3 g of lithium hydroxide monohydrate, 1.2 g of potassium permanganate, 0.1 g of ascorbic acid, and 3 g of anhydrous ethanol, to prepare the magnetic electrode material (Fe3O4@C@LiMn2O4-1:2). The saturation magnetization is 38.17 emu·g. -1 .

[0039] Example 3 The difference from Example 1 lies only in step 2) of the preparation method of the magnetic electrode material. The mass ratio of Fe3O4@C to LiMn2O4 is 1:3, specifically: 0.4 g of Fe3O4@C particles, 0.45 g of lithium hydroxide monohydrate, 1.8 g of potassium permanganate, 0.15 g of ascorbic acid, and 4.5 g of anhydrous ethanol, to prepare the magnetic electrode material (Fe3O4@C@LiMn2O4-1:3). The saturation magnetization is 27.53 emu·g. -1 .

[0040] Example 4 The difference from Example 1 lies only in step 2) of the preparation method of the magnetic electrode material. The mass ratio of Fe3O4@C to LiMn2O4 is 1:5, specifically: 0.4 g of Fe3O4@C particles, 0.9 g of lithium hydroxide monohydrate, 3.0 g of potassium permanganate, 0.25 g of ascorbic acid, and 7.5 g of anhydrous ethanol, to prepare the magnetic electrode material (Fe3O4@C@LiMn2O4-1:5). The saturation magnetization is 12.85 emu·g. -1 .

[0041] Example 5 The difference from Example 1 lies only in step 2) of the preparation method of the magnetic electrode material. The mass ratio of Fe3O4@C to LiMn2O4 is 1:6, specifically: 0.4 g of Fe3O4@C particles, 1.2 g of lithium hydroxide monohydrate, 3.6 g of potassium permanganate, 0.3 g of ascorbic acid, and 9 g of anhydrous ethanol, to prepare the magnetic electrode material (Fe3O4@C@LiMn2O4-1:6). The saturation magnetization is 8.34 emu·g. -1 .

[0042] Example 6 The difference from Example 1 lies only in step 2) of the preparation method of the magnetic electrode material. The mass ratio of Fe3O4@C to LiMn2O4 is 1:7, specifically: 0.4 g of Fe3O4@C particles, 1.5 g of lithium hydroxide monohydrate, 4.2 g of potassium permanganate, 0.35 g of ascorbic acid, and 10.5 g of anhydrous ethanol, to prepare the magnetic electrode material (Fe3O4@C@LiMn2O4-1:7). The saturation magnetization is 5.68 emu·g. -1 .

[0043] Example 7 The only difference from Example 1 is that the solid content of the conductive agent in the anode flow electrode slurry and the cathode flow electrode slurry is 0.5 wt%.

[0044] Example 8 The only difference from Example 1 is that the solid content of the conductive agent in the anode flow electrode slurry and the cathode flow electrode slurry is 0.75 wt%.

[0045] Example 9 The only difference from Example 1 is that the solid content of the conductive agent in the anode flow electrode slurry and the cathode flow electrode slurry is 1.25 wt%.

[0046] Example 10 The only difference from Example 1 is that the conductive agent solid content in the anode flow electrode slurry and the cathode flow electrode slurry is 1.5 wt%.

[0047] Example 11 The only difference from Example 1 is that the magnetic field strength is 10.19 mT.

[0048] Example 12 The only difference from Example 1 is that the magnetic field strength is 15.15 mT.

[0049] Example 13 The only difference from Example 1 is that the magnetic field strength is 25.02 mT.

[0050] Example 14 The only difference from Example 1 is that a simulated salt lake brine system is used as the feed liquid in step (3). Li + The concentration was 162.9747 mg·L⁻¹. -1 Mg 2+ The concentration was 2937.3773 mg·L. -1 Na + The concentration was 5894.636 mg·L⁻¹. -1 and K + The concentration was 1870.153 mg·L⁻¹ -1 Simulated salt lake brine was used as the feed liquid. Five cycles of the experiment were then conducted following the subsequent operating procedure.

[0051] Example 15 A lithium extraction apparatus for implementing the magnetic field-assisted dual-chamber flow electrode continuous cyclic lithium extraction method of Examples 1-13, such as... Figure 1-2As shown, the reactor includes a dual-chamber reactor, a current collector, a magnetic field generator, and a material circulation system connecting the cathode and anode chambers. The dual-chamber reactor is divided into an anode chamber and a cathode chamber by an ion exchange membrane. Both the anode and cathode chambers have liquid inlets and outlets. Electrode slurry is transported from the cathode tank and anode tank to the corresponding chamber's flow channel via peristaltic pumps at a preset flow rate, ensuring stable slurry circulation and efficient mass transfer. Current collectors are installed on both sides of the cathode and anode chambers, with a serpentine flow channel on the side facing the chamber. The current collector is a graphite plate with an electrode area of ​​18.92 cm². 2 .

[0052] The magnetic field generator is an electromagnet, located outside the current collector, and connected to a power source. The material circulation system connecting the cathode and anode chambers includes a cathode tank, an anode tank, a feed brine storage tank, a recovery liquid storage tank, and a solid-liquid separation device. The anode tank is connected to the anode chamber via pipeline and contains the anode flow electrode slurry. The cathode tank is connected to the cathode chamber via pipeline and contains the cathode flow electrode slurry. Both the cathode and anode tanks are equipped with stirring systems that continuously stir the mixed electrode slurry at speeds of 10-3500 rpm.

[0053] Comparative Example 1 The only difference from Example 1 is the preparation method of the magnetic electrode material. It does not contain a carbon coating layer. 0.4 g of Fe3O4 particles were added to deionized water, followed by 0.6 g of lithium hydroxide monohydrate. After stirring for 0.5 h, 2.4 g of potassium permanganate, 0.2 g of ascorbic acid, and 6 mL of anhydrous ethanol were added. The mixture was reacted at room temperature for 2 h, then transferred to a 200 mL reactor and reacted at 180 °C for 5 h. The heating rate during the heating process was 5 °C·min. -1 After the reaction was completed, magnetic separation was performed using a magnet, and the supernatant was washed with deionized water and anhydrous ethanol until it was completely clear. The supernatant was then dried in a vacuum drying oven at 60 °C for 12 h. Finally, a magnetic electrode material, Fe3O4@LiMn2O4, was obtained with lithium manganese oxide grown in situ on the outer layer of Fe3O4, wherein the mass ratio of Fe3O4 to LiMn2O4 was also 1:4 (Fe3O4@LiMn2O4-1:4). Following the experimental method in Example 1, delithiation was first performed to obtain Fe3O4@HMn2O4, which was used as the cathode chamber electrode material.

[0054] Comparative Example 2 The only difference from Example 1 is that the preparation method of the magnetic electrode material is different. Physical mixing is used to prepare the electrode slurry by physically mixing Fe3O4@C particles with LiMn2O4 (Fe3O4@C+LiMn2O4-1:4) and a conductive agent.

[0055] Comparative Example 3 The only difference from Example 1 is that no magnetic field is applied.

[0056] Comparative Example 4 Lithium extraction experiments were conducted using the Fe3O4@LiMn2O4-1:4 material from Comparative Example 1 in a device without a magnetic field.

[0057] Comparative Example 5 Lithium extraction experiments were conducted using the Fe3O4@C+LiMn2O4-1:4 material from Comparative Example 2 in a device without a magnetic field.

[0058] Performance Testing and Analysis Magnetic electrode materials prepared from Fe3O4@C and LiMn2O4 at different mass ratios were subjected to XRD analysis, and their XRD patterns are shown below. Figure 3 As shown, the diffraction peaks at 18.61°, 36.08°, 37.74°, 43.86°, 58.05°, and 63.78° for each sample correspond to the (111), (311), (222), (400), (511), and (440) crystal planes of LiMn2O4 (JCPDS No. 35-0782), respectively, indicating that samples with different proportions successfully formed spinel-structured LiMn2O4. Meanwhile, each sample retained the characteristic diffraction peaks of Fe3O4, indicating that the Fe3O4 crystal structure was not significantly damaged during the composite process, and no other impurity peaks were detected, suggesting that the prepared composite material has high phase purity. With increasing LiMn2O4 content, the intensity of characteristic peaks belonging to Fe3O4 decreased to varying degrees. This is mainly attributed to the increased coating amount of LiMn2O4 on the Fe3O4@C surface, which reduces the relative diffraction contribution of Fe3O4, rather than being caused by the destruction of the Fe3O4 crystal structure. XRD results show that Fe3O4@C@LiMn2O4 composite materials with different mass ratios have been successfully prepared.

[0059] In the examples and comparative examples, lithium extraction was performed continuously for 4 hours. Based on the lithium ion concentration measured by ICP (inductively coupled plasma) method, the lithium extraction rate (η), average lithium extraction rate, and charge efficiency (CE) of the system were calculated. The test results are shown in Table 1.

[0060] The formula is as follows: Lithium extraction rate ; Average lithium extraction rate = ; Charge efficiency ; Where C0 is Li + The initial concentration, C t It is Li +The concentration at time t, where F is the Faraday constant (96485 C·mol⁻¹). -1 M is the molar mass of Li, A is the total contact area between the flowing electrode slurry and the current collector, and I is the current at time t.

[0061] Table 1

[0062] Table 1 shows that the lithium extraction performance of different magnetic lithium intercalation / deintercalation composite materials in Examples 1-6 varies with the mass ratio of Fe3O4@C to LiMn2O4 during lithium extraction in a magnetic field-assisted device. Under the same initial lithium ion concentration, flow electrode slurry composition, operating voltage, circulation flow rate, magnetic field strength, and running time, the lithium extraction performance of composite particles with different Fe3O4@C to LiMn2O4 mass ratios was tested. The results show that when the mass ratio of Fe3O4@C to LiMn2O4 increases from 1:2 to 1:4, the lithium extraction rate, lithium extraction speed, and charge efficiency of the system gradually increase; when the mass ratio continues to increase to 1:7, the three indicators gradually decrease. Among them, the composite particles with a mass ratio of 1:4 exhibit higher lithium extraction performance, with a lithium extraction rate of 87.32% and a lithium extraction speed of 0.0264 mg·cm⁻¹. -2 ·min -1 The charge efficiency is 86.98%. This may be because an appropriate amount of LiMn2O4 can provide sufficient lithium-ion insertion sites while retaining the role of the Fe3O4@C magnetic conductive core. When the LiMn2O4 loading is too low, the number of active sites is insufficient, while when the loading is too high, the thicker LiMn2O4 layer will increase the electron transport resistance and reduce the content of magnetic components per unit mass of composite particles.

[0063] The effect of applying an external magnetic field on lithium extraction performance was investigated for Fe3O4@C@LiMn2O4-1:4 (Example 1, Comparative Example 3 without magnetic field), Fe3O4@LiMn2O4 (Comparative Example 1, Comparative Example 4 without magnetic field), and a physical mixture of Fe3O4@C and LiMn2O4 (Comparative Example 2, Comparative Example 5 without magnetic field). Without an applied magnetic field, the lithium extraction rates of the three materials were 62.31%, 53.37%, and 46.59%, respectively, with extraction rates of 0.0189 mg·cm⁻¹. -2 ·min -1 0.0162 mg·cm -2 ·min -1 and 0.0141 mg·cm -2 ·min -1The charge efficiencies were 62.13%, 53.22%, and 46.46%, respectively. After applying an external magnetic field, the lithium extraction rates of the three materials increased to 87.32%, 67.49%, and 58.61%, respectively, and the lithium extraction rates increased to 0.0264 mg·cm⁻¹. -2 ·min -1 0.0204 mg·cm -2 ·min -1 and 0.0177 mg·cm -2 ·min -1 The charge efficiencies were increased to 86.98%, 67.32%, and 58.44%, respectively. Compared with the condition without a magnetic field, the lithium extraction rate of all three materials was improved under the action of an applied magnetic field. Among them, the lithium extraction rate of the Fe3O4@C@LiMn2O4-1:4 core-shell composite material was improved by 24.92 percentage points, a relative improvement of about 39.99%, which is higher than that of the carbon-free material and the physical hybrid material. The above results indicate that the magnetic component of Fe3O4 enables the active particles to respond to the applied magnetic field, promotes the migration of particles to the vicinity of the current collector, and increases the effective contact between particles and between particles and the current collector, thereby improving charge transport and Li-Li extraction in the flow electrode. + The embedding and extraction process. Further comparison of the three materials reveals that the intermediate carbon layer improves the interfacial contact and electron transport between the magnetic core and the LiMn2O4 active layer, while the in-situ grown core-shell structure avoids the problem of unstable contact between components in physically mixed materials. Therefore, the Fe3O4@C@LiMn2O4 core-shell composite material exhibits high lithium extraction rate, lithium extraction efficiency, and charge efficiency under an applied magnetic field, demonstrating the synergistic effect between magnetic response characteristics, carbon layer conductivity, and the core-shell structure.

[0064] Data from 4 hours of operation of the flow electrode under different conductive agent solid contents (Examples 1 and 7-10) show that when the conductive agent solid content increases from 0.5 wt% to 1.0 wt%, the lithium extraction rate increases from approximately 40.19% to 87.32%, and the average lithium extraction rate increases from 0.0122 mg·cm⁻¹. -2 ·min -1 Increased to 0.0264 mg·cm⁻¹ -2 ·min -1 The increase was most significant. This indicates that appropriately increasing the conductive agent content can effectively improve the electronic conduction network of the flowing electrode slurry, reduce the ohmic impedance inside the electrode, and thus promote the insertion and extraction reactions of lithium ions on the surface of the magnetic electrode material. When the solid content of the conductive agent continued to increase to 1.25 wt% (Example 9) and 1.5 wt% (Example 10), the increase in lithium extraction rate and extraction yield decreased significantly. Considering both lithium extraction performance and slurry flowability, the best overall effect was achieved when the solid content of the conductive agent was 1.0 wt%.

[0065] Examples 1 and 11-13 tested the delithiation performance by applying different magnetic field strengths, and the results are as follows: Figure 4 As shown, when the magnetic field strength is controlled at 20.12 mT, the entire lithium extraction system exhibits the best overall performance and cycle stability. This phenomenon indicates that under the action of a suitable magnetic field, the active sites inside the electrode material are fully exposed and activated, and the electrode particles undergo a significant activation process, thus slightly improving the initial lithium extraction performance. As the number of cycles continues to increase, affected by factors such as the gradual passivation of the active sites of the electrode material and the accumulation of side reactions, the overall lithium extraction rate shows a slow downward trend, but the decline is significantly lower than that of the control system under no magnetic field or other magnetic field strengths, and the decay rate is effectively suppressed. Even after 10 consecutive cycles, the system can still maintain a lithium extraction rate of 78%, and the corresponding capacity retention is close to 89.22%.

[0066] Example 14: After conducting five cycles of lithium extraction experiments in simulated salt lake brine containing various ions, the results are as follows... Figure 5 As shown. During the first to fifth cycles, Li + / Mg 2+ The separation coefficients were 951.58, 898.90, 812.35, 790.85, and 767.78, respectively. + / Na + The separation coefficients were 343.83, 296.02, 276.99, 264.52, and 258.55, respectively. + / K + The separation coefficients were 75.57, 66.56, 61.74, 59.24, and 57.59, respectively. With increasing cycle number, all three separation coefficients showed a slow decreasing trend, which may be related to the decreased utilization of some active sites during multiple lithium insertion and delithiation processes, and the gradual accumulation of coexisting ions on the particle surface; however, after five cycles, the Li... + Relative to Mg 2+ Na + and K + The separation coefficients remained at 767.78, 258.55, and 57.59, respectively, indicating that the magnetic composite particles effectively separated Li under multi-ion coexistence conditions. + It exhibits high selectivity and maintains relatively stable ion separation capability during continuous cycling. These results indicate that the LiMn2O4 active layer can preferentially embed Li using its lattice channels and ion size matching relationship. + , while Mg 2+ Na + and K + It is difficult to enter the lattice structure of the active layer, thereby realizing Li +Selective separation from coexisting ions; at the same time, the Fe3O4 magnetic core enables the active particles after the reaction to be rapidly separated and recycled by an external magnetic field, which is beneficial to maintaining the material utilization efficiency in the continuous lithium extraction process.

[0067] This invention achieves a lithium extraction rate of 87.32% under low slurry solid content (3.0 wt%) by synergistically designing a Fe3O4@C@LiMn2O4 core-shell structured magnetic electrode material and a magnetic field-assisted dual-chamber flow electrode system. The lithium extraction rate remains above 78% within 10 cycles, verifying the synergistic effect between magnetic response characteristics, carbon layer conductivity, and core-shell structure, as well as the stability and practicality of the continuous closed-loop cyclic lithium extraction system.

[0068] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several modifications and improvements can be made without departing from the inventive concept, and these all fall within the protection scope of the present invention.

Claims

1. A method for continuous cyclic lithium extraction using a magnetic field-assisted dual-chamber flow electrode, characterized in that, Includes the following steps: (1) Slurry preparation: The magnetic electrode material and conductive agent are added to the recovery liquid and mixed evenly to obtain the anode flow electrode slurry. The lithium-poor magnetic electrode material obtained by delithiation treatment is added to lithium-containing brine and mixed evenly to obtain a cathode flow electrode slurry; the magnetic electrode particles are Fe3O4@C@LiMn2O4 and the mass ratio of Fe3O4@C to LiMn2O4 is 1:2 to 1:

7. (2) The cathode flow electrode slurry and the anode flow electrode slurry are respectively delivered to the cathode chamber and the anode chamber by a peristaltic pump; (3) Under the action of an external power supply and a magnetic field, the lithium-depleted magnetic electrode material in the cathode chamber selectively inserts lithium ions from the lithium-containing brine, and the magnetic electrode material in the anode chamber undergoes a delithiation reaction, releasing lithium ions into the recovery liquid. At the same time, anions migrate through the ion exchange membrane to maintain the charge balance in the cathode and anode chambers. The magnetic field is provided by a magnetic field generating device located on both sides of the anode and cathode chambers, and the magnetic field strength is 10 to 30 mT. The operating voltage of the external power supply is 0.5 to 2.0 V. (4) The anolyte and cathode slurry after the reaction are returned to their respective storage tanks and separated into solid and liquid by a solid-liquid separation device using the magnetic response characteristics of the magnetic electrode material. (5) The lithium-poor brine obtained from the separation is discharged and collected. The delithiated magnetic electrode material is mixed with the newly replenished lithium-containing brine and returned to the cathode tank. The lithium-rich recovery liquid obtained from the separation is collected. The lithium-intercalated magnetic electrode material is mixed with the recovery liquid and returned to the anode tank for delithiation. (6) Continuously replenish lithium-containing brine to the cathode tank to replenish the lithium ion loss caused by continuous lithium resource extraction, maintain the stable concentration of lithium ions in the system, and form a continuous closed-loop lithium extraction system.

2. The magnetic field-assisted dual-chamber flow electrode continuous cyclic lithium extraction method according to claim 1, characterized in that, The preparation method of the magnetic electrode material includes: adding Fe3O4@C particles to deionized water, then adding lithium hydroxide monohydrate, stirring, adding potassium permanganate, ascorbic acid and anhydrous ethanol, reacting at room temperature, transferring to a reaction vessel for hydrothermal reaction at 150-200 ℃ for 3-8 h, and after the reaction is completed, magnetic separation, washing and drying are performed to obtain the magnetic electrode material.

3. The magnetic field-assisted dual-chamber flow electrode continuous cyclic lithium extraction method according to claim 1, characterized in that, The magnetic field strength is 10.19-25.02 mT, and the operating voltage of the external power supply is 0.5-1.5 V.

4. The magnetic field-assisted dual-chamber flow electrode continuous cyclic lithium extraction method according to claim 1, characterized in that, The solid content of the magnetic electrode material and the conductive agent in the anode flowing electrode slurry is 1.0-5.0 wt% and 0.5-1.5 wt%, respectively. The solid content of the lithium-depleted magnetic electrode material and the conductive agent in the cathode flowing electrode slurry is 1.0-5.0 wt% and 0.5-1.5 wt%, respectively. The electrolyte content is 10-300 mg·L⁻¹. -1 LiCl solution.

5. The method for continuous lithium extraction using a magnetic field-assisted dual-chamber flow electrode according to claim 1, characterized in that, The lithium-poor magnetic electrode material is obtained by placing a magnetic electrode material in an HCl solution for lithium removal, with the chemical formula Fe3O4@C@HMn2O4.

6. The method for continuous lithium extraction using a magnetic field-assisted dual-chamber flow electrode according to claim 1, characterized in that, The circulation rate of the flow electrode slurry is 0-100 mL / min. -1 .

7. The magnetic field-assisted dual-chamber flow electrode continuous cyclic lithium extraction method according to claim 1, characterized in that, The lithium-containing brine includes one or more of the following: seawater, concentrated seawater, salt lake brine, concentrated brine, brine pretreated by membrane filtration or solar pond evaporation, and lithium-containing waste liquid recovered after lithium battery production or use. The recovered liquid is pure water or lithium salt solutions of different concentrations.

8. A lithium extraction apparatus for implementing the magnetic field-assisted dual-chamber flow electrode continuous circulation lithium extraction method according to any one of claims 1-7, characterized in that, include: A dual-chamber reactor is divided into an anode chamber and a cathode chamber by an anion exchange membrane, with current collectors provided on both sides of the cathode chamber and the anode chamber respectively; A magnetic field generating device is placed outside the current collector. The magnetic field generating device includes one of a permanent magnet, a solenoid, a Helmholtz coil, and an electromagnet. When the magnetic field generating device is an electromagnetic magnetic field generating device, it is connected to a magnetic field power supply. The material circulation system connecting the cathode chamber and the anode chamber includes a cathode tank, an anode tank, a feed brine storage tank, a recovery liquid storage tank, and a solid-liquid separation device. The anode tank is connected to the anode chamber through a pipeline, and the anode flow electrode slurry is placed in the anode tank. The cathode tank is connected to the cathode chamber through a pipeline, and the cathode flow electrode slurry is placed in the cathode tank.

9. The lithium extraction apparatus according to claim 8, characterized in that, Both the anode chamber and the cathode chamber are equipped with liquid inlets and outlets. The anode flow electrode slurry and the cathode flow electrode slurry are respectively transported to the anode chamber and the cathode chamber by peristaltic pumps.

10. The lithium extraction apparatus according to claim 8, characterized in that, The anion exchange membrane is either a homogeneous membrane or a heterogeneous membrane; the cathode tank and anode tank are equipped with a stirring system.